2022
DOI: 10.1111/cgf.14613
|View full text |Cite
|
Sign up to set email alerts
|

Learning Human Viewpoint Preferences from Sparsely Annotated Models

Abstract: View quality measures compute scores for given views and are used to determine an optimal view in viewpoint selection tasks. Unfortunately, despite the wide adoption of these measures, they are rather based on computational quantities, such as entropy, than human preferences. To instead tailor viewpoint measures towards humans, view quality measures need to be able to capture human viewpoint preferences. Therefore, we introduce a large-scale crowdsourced data set, which contains 58k annotated viewpoints for 32… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
3
0

Year Published

2024
2024
2024
2024

Publication Types

Select...
4
1

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(3 citation statements)
references
References 37 publications
0
3
0
Order By: Relevance
“…Deep-learning approaches [21] select the optimal viewpoint by conducting multi-view renderings through a predefined sequence of viewpoints, then identifying the optimal viewpoint according to a learned sequence of view scores. Although these approaches effectively capture human selection preferences, they face two primary challenges in practical applications: first, they require extensive pre-rendering of views, which consumes significant resources and might overlook the optimal viewpoints; second, obtaining large-scale human-annotated data is costly and labor-intensive.…”
Section: Deep-learning Based Approachesmentioning
confidence: 99%
“…Deep-learning approaches [21] select the optimal viewpoint by conducting multi-view renderings through a predefined sequence of viewpoints, then identifying the optimal viewpoint according to a learned sequence of view scores. Although these approaches effectively capture human selection preferences, they face two primary challenges in practical applications: first, they require extensive pre-rendering of views, which consumes significant resources and might overlook the optimal viewpoints; second, obtaining large-scale human-annotated data is costly and labor-intensive.…”
Section: Deep-learning Based Approachesmentioning
confidence: 99%
“…Hartwig et al [ 36 ] introduced a neural view quality measure aligned with human preferences. The study demonstrated that this measure generalized not only to models unseen during training but also to unseen model categories.…”
Section: State Of the Artmentioning
confidence: 99%
“…A reliable method to evaluate the ambiguity of a scatterplot is directly measuring perceptual variability via human experiments [26]. However, this process is costly and not scalable.…”
Section: Introductionmentioning
confidence: 99%